Heat shock protein response to stress in poultry: A review - Balakrishnan, Krishnan Nair; Ramiah, Suriya Kumari; Zulkifli, Idrus (MDPI, 2023)
Compared to other animal species, production has dramatically increased in the poultry sector. However, in intensive production systems, poultry are subjected to stress conditions that may compromise their well-being. Much like other living organisms, poultry respond to various stressors by synthesising a group of evolutionarily conserved polypeptides named heat shock proteins (HSPs) to maintain homeostasis. These proteins, as chaperones, play a pivotal role in protecting animals against stress by re-establishing normal protein conformation and, thus, cellular homeostasis. In the last few decades, many advances have been made in ascertaining the HSP response to thermal and non-thermal stressors in poultry. The present review focuses on what is currently known about the HSP response to thermal and non-thermal stressors in poultry and discusses the factors that modulate its induction and regulatory mechanisms. The development of practical strategies to alleviate the detrimental effects of environmental stresses on poultry will benefit from detailed studies that describe the mechanisms of stress resilience and enhance our understanding of the nature of heat shock signalling proteins and gene expression.